2022
DOI: 10.3389/fpsyg.2022.1002275
|View full text |Cite
|
Sign up to set email alerts
|

“We buy what we wanna be”: Understanding the effect of brand identity driven by consumer perceived value in the luxury sector

Abstract: Prior studies focused on consumer satisfaction and loyalty have brought undeniable benefits to luxury brand marketing but are not sufficient to ensure a long-lasting and profitable customer-brand relationship in the new setting. Brand identity provides a valuable exploration of this issue. However, the current measurement of brand identity is relatively simple, and there is no clear answer to what factors encourage brand identity development. This study attempts to address this gap by dividing the brand identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 85 publications
0
3
0
Order By: Relevance
“…In addition, the current study solely examined the moderating effect of individuals’ salient personal/social identities, yet the potential impact of brand identity (i.e. consumers’ perception of the brand, including personal/social identities) warrants further exploration (Xi et al , 2022). Future studies could delve into how the results might differ when considering varied brand identities or the fit between consumers and brand identity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the current study solely examined the moderating effect of individuals’ salient personal/social identities, yet the potential impact of brand identity (i.e. consumers’ perception of the brand, including personal/social identities) warrants further exploration (Xi et al , 2022). Future studies could delve into how the results might differ when considering varied brand identities or the fit between consumers and brand identity.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, crowdsourcing virtual communities with high information quality offer users real, effective, rich, interesting, and timely information. Users derive a strong sense of value from such information [ 84 ], which helps them form an identity and attachment to the community. This encourages users to become community members and establishes a sense of community identification [ 85 , 86 ].…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Previous studies have indicated that a positive evaluation of design not only boosts the desire to own a product [1] but also increases the willingness to pay more for it [2]. Furthermore, an appealing design fosters a sense of pride and care in the use of the product, while also aiding in the formation of an individual identity [3]. This phenomenon has expanded the range of products that are appreciated by individual consumers, showcasing the evolving impact of design [4].…”
Section: Introductionmentioning
confidence: 99%